Crenças de duas professoras de inglês em pré-serviço a respeito de falantes de língua inglesa e de suas respectivas culturas: um estudo de caso - Tatiana Diello Borges (2007)
This research was carried out at an Extension Center at a Government-owned university in southeastern Brazil and it aimed at (1) identifying and analyzing the beliefs held by two pre-service English teachers about English speakers and their respective cultures and at (2) understanding how these teachers justify such beliefs. The theoretical framework was based on studies in the field of foreign language teaching/learning that focused on the issue of beliefs (Pajares, 1992; Gimenez, 1994; Johnson, 1994; Barcelos, 1995; Almeida Filho, 1999; Horwitz, 1999; Silva, 2001) and identity, also taking into account the issue of imagined communities (Hall, 1997; Rajagopalan, 2003; Norton, 2001; Kanno e Norton, 2003; Brun, 2004; Murphey, Jin e Li-Chi, 2004). The case study methodology was employed and the following data collection tools were used: questionnaires, interviews, class observations (supported by field notes and audio recordings), and group discussion. The results obtained suggest that the teachers beliefs and justifications about North-American and Irish people, as well as about their culture, are in general similar. Results also showed that both teachers identify themselves partially with the United States and fully with the Ireland, the two most oft-mentioned imagined communities. This study shows how important it is to seriously engage both language learners and teachers beliefs about their imagined communities, as these can encourage or hinder students and teachers investment in the languageteaching/learning process.